THE EVALUATION FREQUENCY OF THE DISCRETE-EXPONENTIAL SIGNAL - Дем’яник, Д. (Science-based technologies, 2011)
Efficiencies of orthogonal transformations in bases of discrete-exponential functions and functions of Vilenkin–Chrestenson were compared.